Konflik Moro Sebagai Ancaman Identitas Nasional Filipina Selatan dan Dampaknya pada Kohesi Politik ASEAN - Dewi Erlina; Elly Nurlia (Jurnal Transformasi Global, 2025)
The Moro conflict in the Southern Philippines is rooted in postcolonial structural marginalization and failed integration, posing a serious threat to Philippine national identity. The purpose of this study is to analyze the Moro conflict as a threat to national identity and its impact on ASEAN political cohesion, using Benedict Anderson's Imagined Communities Theory framework. The method used is a qualitative literature study approach, as data collection utilized secondary data analysis from credible journals and academic documents. The results show that the failure of the Philippine national narrative to create bonds of equal solidarity, as envisioned by Anderson, has triggered the emergence of a separate "Bangsamoro" superordinate identity that rejects a homogeneous Filipino identity. This identity polarization has given rise to a separatist generation of the MNLF, MILF, and the radical Abu Sayyaf group. Regionally, this conflict threatens ASEAN cohesion through security spillover and transnational criminality in the Sulu Sea, forcing ASEAN to develop collective security cooperation mechanisms, such as the Trilateral Maritime Patrol. Conflict resolution through the implementation of the Bangsamoro Organic Law (BOL) is considered crucial for strengthening Philippine national integrity and maintaining regional stability.